Nineteenth century China: five imperialist perspectives, - Basu, Dilip K. (Michigan papers in Chinese studies, 1972)
Materials from the past that wrongly anticipate the future, or present information or judgments that are later proved misleading or erroneous, are sometimes overlooked in reconstructing the past. Yet such documents are as legimiate, and perhaps as important, as those that are vindicated by events or continue to share perspectives with later generations. Materials from the past that wrongly anticipate the future, or present information or judgments that are later proved misleading or erroneous, are sometimes overlooked in reconstructing the past. Yet such documents are as legitimate, and perhaps as important, as those that are vindicated by events or continue to share perspectives with later generations. The first two texts in Nineteenth-Century China exemplify the imperialist mind's eagerness to explore the world, to get a picture of all of its parts, and as rapidly as possible to "open" all areas to the benificent influence of the West, notably through an expanded commerce that would enrich its Western masters. Samuel Ball's "Observations" (1817) show how much detailed information was available to Westerners and what the mercantile British were after, and an anonymous dissertation (1838) provides an example of the dream of the China as El Dorado: an immense population of eager traders, hard workers, and willing buyers. The third text (1845) is an early foreshadowing by a colonial official, R. M. Martin, of Western imperial arguments, rationalizations, and attitudes that would become common fifty years later. The fourth selection consists of an exchange of correspondence in 1847 about British access to and use of land in the vicinity of Canton. A short statement of purpose (1848) from the Morrison Education Society, demonstrating a missionary enterprise combining Christian evangelism and English education, concludes the book. -- publisher's website